The silent threat: asymptomatic parasitemia and malaria transmission - Lindblade, Kim A; Steinhardt, Laura; Samuels, Aaron; Kachur, S Patrick; Slutsker, Laurence (Expert review of anti-infective therapy, 2013)
Scale-up of malaria control interventions has resulted in a substantial decline in global malaria morbidity and mortality. Despite this achievement, there is evidence that current interventions alone will not lead to malaria elimination in most malaria-endemic areas and additional strategies need to be considered. Use of antimalarial drugs to target the reservoir of malaria infection is an option to reduce the transmission of malaria between humans and mosquito vectors. However, a large proportion of human malaria infections are asymptomatic, requiring treatment that is not triggered by care-seeking for clinical illness. This article reviews the evidence that asymptomatic malaria infection plays an important role in malaria transmission and that interventions to target this parasite reservoir may be needed to achieve malaria elimination in both low- and high-transmission areas.